Peran Perkembangan Teknologi dalam Penyebaran Dhamma: Kajian Media Digital dan Praktik Buddhisme di Era Kontemporer - Hendriyani Setianingsih (Jurnal Budi Pekerti Agama Buddha, 2025)
In the advancement of information technology and technology in the modern era, it certainly has a considerable impact on various areas of life, including in the spread of religious teachings, one of which is Buddhism. The method of delivering the Dhamma today does not only use traditional approaches such as lectures or Dhammadesana in monasteries or live teachings, but now it can be through digital media such as Youtube, social media, applications, or online videos. This article reviews how technology plays an important role as a tool that can reach more people around the world without being limited by space and time. Through the various uses of these technological developments, the teachings of the Dhamma are presented in a more interesting, interactive, and easily accessible form for all groups, such as audio-visuals, digital books, podcasts, and application-based online classes. In addition, technology also allows for virtual discussion forums, sharing of spiritual experiences, and digital preservation of Buddhist texts. Thus, the use of appropriate technological developments can support the sustainability, development, and spread of the Dhamma so that it remains relevant, sustainable, and beneficial to today's society and future generations.